Upaństwowienie przedszkoli żydowskich w Polsce „ludowej” - Wiśniewska, Monika (Biuletyn Historii Wychowania, 2019)
Educational and teacher training institutions for Jewish children and adolescents had a long and well-established tradition in Poland. Institutional forms of preschool education call for special attention, all the more so that the remaining national and ethnic minorities did not run their own kindergartens in Poland after WWII. In these circumstances, Jewish kindergartens were a striking exception. Ultimately, they suffered the same fate as the other educational and teacher training institutions managed by entities not welcomed by the Communist party and government in Poland, inspired by Marx’s and Lenin’s ideologies, whose guidelines from the communist headquarters in Moscow imposed a monopolistic vision of so-called socialist education and upbringing.